Dapagliflozin alleviates renal fibrosis in a mouse model of adenine-induced renal injury by inhibiting TGF-β1/MAPK mediated mitochondrial damage - Zeng, Jianhua; Huang, Hao; Zhang, Yan; Lv, Xin; Cheng, Jiawei; Zou, Si Jue; Han, Yuanyuan; Wang, Songkai; Gong, Li; Peng, Zhangzhe (Frontiers in Pharmacology, 2023)
Renal fibrosis is a common pathological outcome of various chronic kidney diseases, and as yet, there is no specific treatment. Dapagliflozin has shown renal protection in some clinical trials as a glucose-lowering drug, but its role and mechanism of action in renal fibrosis remain unclear. In this study, we used a 0.2% adenine diet-induced renal fibrosis mouse model to investigate whether dapagliflozin could protect renal function and alleviate renal fibrosis in this animal model. We found that dapagliflozin’s protective effect on renal fibrosis was associated with (1) sustaining mitochondrial integrity and respiratory chain complex expression, maintained the amount of mitochondria; (2) improving fatty acid oxidation level with increases in CPT1-α, PPAR-α, ACOX1, and ACOX2; (3) reducing inflammation and oxidative stress, likely via regulation of IL-1β, IL-6, TNF-α, MCP-1, cxcl-1 expression, and glutathione (GSH) activity, superoxide dismutase (SOD) and malondialdehyde (MDA) levels; and (4) inhibiting the activation of the TGF-β1/MAPK pathway. In HK2 cells treated with TGF-β1, dapagliflozin protected mitochondria, improved mitochondrial respiratory chain complex expression, and inhibited activation of the TGF-β1/MAPK pathway.